DESAIN DAN IMPLEMENTASI SOFTWARE AS SERVICE PADA PENGELOLAAN ABSENSI KEDISIPLINAN MAHASISWA POLITEKNIK NEGERI LAMPUNG - Halim Fathoni; Eko Win Kenali (IIB Darmajaya, 2014)
Cloud computing and the Internet is the latest generation in the world of information technology (IT). This technology allows an organization to save costs IT infrastructure investments, in general, the organization that will use IT must build a data center that consists of multiple servers and build a whole needs supporters such as backup power, data backup and others are certainly in need of funds a little. With cloud computing technology was submitted burden on providers including peraawatan costs. Based on the type of service it, cloud computing is divided into three: SaaS (Software as a Service), PaaS (Platform as a Service), and IaaS (infrastruture as a Service) (Juan, 2012). SaaS is an application that is intended to be used multiple users and invested in cloud Infrastructure generally accessed through the Internet by using a browser (firefox, chrome, etc.). In the traditional way of software deployed by installing on a desktop computer and its common one license for each computer. In the SaaS application can be used without having to install on the computer (Juan, 2012). This research emphasizes on how to build software based on SaaS and it’s implementing POLINELA. Of these activities is expected to be dug deeper into the advantages and weaknesses of this technology. Attendance management discipline problems solved by the students try to build software based on SaaS. With this technology officer can enter data from anywhere and at anytime, except that students can check without having to make noise in the room departmentKeywords: Currently, Attendance, Lecturer Guardian, loud